1997
DOI: 10.1364/josab.14.003277
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the collision-based Xe VI and Xe VII spectra

Abstract: Collision-based spectroscopy of a Xe qϩ (q ϭ 6, 7) beam with a target T (T ϭ Na, Ar) has been performed in the 35-800-nm wavelength region. Twenty-five new Xe VI lines and twenty-two new Xe VII lines were classified, twelve new energy levels of Xe VI and nine new energy levels of Xe VII were established, and one energy level of Xe VI was revised from the classified transitions. The analysis was supported by Hartree-Fock calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
2
11
1
2
Order By: Relevance
“…Table 3 shows the set of 243 lines observed in our experiments, 146 of which were determined for the first time. Another 37 lines, from Larsson et al (1996), Wang et al (1996), and Wang et al (1997a), are shown with revised wavelengths as we measured them with a lower uncertainty. Observed line intensities given in this table are visual estimates of the blackening of the photographic plates.…”
Section: Transition Rates Oscillator Strengths and Lifetimesmentioning
confidence: 95%
See 2 more Smart Citations
“…Table 3 shows the set of 243 lines observed in our experiments, 146 of which were determined for the first time. Another 37 lines, from Larsson et al (1996), Wang et al (1996), and Wang et al (1997a), are shown with revised wavelengths as we measured them with a lower uncertainty. Observed line intensities given in this table are visual estimates of the blackening of the photographic plates.…”
Section: Transition Rates Oscillator Strengths and Lifetimesmentioning
confidence: 95%
“…a Uncertainty: New and revised wavelengths below 2100 Å: 0.02 Å; New and revised wavelengths above 2100 Å: 0.01 Å; Kaufman & Sugar (1987); Tauheed et al (1992); Churilov & Joshi (2000): 0.005 Å; Reyna Almandos et al 2001: 0.02 Å. b Hartree-Fock relativistic + core polarization: for 5s 2 nl − 5s 2 n 0 l 0 transitions α = 5.80a 0 3 ; for transitions involving unfilled 5s subshell, α = 0.993a 0 3 . c References: (1) Kaufman & Sugar 1987; (2) Tauheed et al 1992; (3) Larsson et al 1996;(4) Wang et al 1996;(5) Wang et al 1997a;(6) Wang et al 1997b…”
Section: Complex N =mentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the energy level values reported by Wang et al [25] (compiled by Saloman [38]) for 3 D 1,2,3 of 5s6d and 3 S 1 of 5s7s configurations. We reported new energy level values for 1 D 2 of 5s6d, 1 S 0 of 5s7s, 1 P 1 of 5s7p configurations and 7 new energy level values for 4d 9 5s 2 5p configuration of Xe VII spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Larsson et al [24] obtained energy levels of the 5s6s, 5s5d and 5p 2 , and 5s4f configurations by collision-based spectroscopy. Using the [25] extended Larsson's work to include the 5s(6p + 7p) and 5s(6d + 7s) configurations. The study of the 5p5d configuration by Cavalcanti et al using a theta-pinch as light source [26], by Gallardo et al, reporting fourteen new energy levels and one hundred and ten new lines using a pulsed discharge [27], was made.…”
Section: Introductionmentioning
confidence: 99%